2018
DOI: 10.1021/acs.analchem.8b02659
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Selectivity of Ion-Selective Electrodes Interpreted Using the Nernst-Planck-Poisson Model

Abstract: The Nernst-Planck-Poisson model is used for modeling the sensitivity and selectivity of ion-selective electrodes (ISEs) with plastic membranes. Two pivotal parameters characterizing ISE response are in focus: sensitivity and selectivity. An interpretation of sensitivity, which considers the concurrent influence of anions and cations on the ISE slope, is presented. The interpretation of selectivity shows the validity and limits of approaches hitherto taken to measure the true (unbiased) selectivity coefficient.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Jasielec et al used the NPP model to confirm the validity and limits of the method proposed by Egorov and co-workers. 54 The calculations showed that this method works well in the range of medium selectivity coefficients values, provided that the primary ion contamination of the sample (for example, from the impurities in the interfering ion salts) can be avoided. Unfortunately, for very high selectivity coefficients values (Log K ij Pot < −7.0), the extrapolation gives negative results, and other methods should be used.…”
Section: ■ Theory Of Potentiometric Responsementioning
confidence: 97%
See 1 more Smart Citation
“…Jasielec et al used the NPP model to confirm the validity and limits of the method proposed by Egorov and co-workers. 54 The calculations showed that this method works well in the range of medium selectivity coefficients values, provided that the primary ion contamination of the sample (for example, from the impurities in the interfering ion salts) can be avoided. Unfortunately, for very high selectivity coefficients values (Log K ij Pot < −7.0), the extrapolation gives negative results, and other methods should be used.…”
Section: ■ Theory Of Potentiometric Responsementioning
confidence: 97%
“…The approach is an extension of earlier work by Egorov’s group that only treated equally charged ions. Jasielec et al used the NPP model to confirm the validity and limits of the method proposed by Egorov and co-workers . The calculations showed that this method works well in the range of medium selectivity coefficients values, provided that the primary ion contamination of the sample (for example, from the impurities in the interfering ion salts) can be avoided.…”
Section: Theory Of Potentiometric Responsementioning
confidence: 99%
“…A decade later, an efficient simulation procedure for multi-component NPP equations using the first fully implicit (predictive) finite difference time scheme was presented by Brumleve and Buck [13]. Their approach to the numerical treatment of NPP has been used in numerous papers in electrochemistry of ion-selective membranes [27][28][29][30][31][32][33][34][35][36][37]. Other numerical methods proposed for the solution of the NPP problem include fast implicit finite difference [38], finite element [39][40][41][42], and network simulation [43][44][45].…”
Section: The Nernst-planck-poisson Modelmentioning
confidence: 99%
“…The NPP model has been successfully used for the description of a large variety of electrochemical sensors used in potentiometry [31][32][33][34][35][36][37]47] and impedance spectroscopy [13,48,49]. That includes the NPP description of neutral carrier electrodes [50], solid-contact electrodes [51], coated-wire electrodes [52], and ion-selective field effect transistors [52].…”
Section: The Nernst-planck-poisson Modelmentioning
confidence: 99%
“…The concept of a single-ion partition coefficient first introduced by Eisenman [ 1 ] is widely used in the theoretical description of the functioning of ion-selective electrodes (ISEs) and optodes [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. According to [ 1 ], a single-ion partition coefficient depends on standard Gibbs energies of hydration and solvation.…”
Section: Introductionmentioning
confidence: 99%